Long-Term Radiographic Adaptations to Stress of High-Level and Recreational Rock Climbing in Former Adolescent Athletes: An 11-Year Prospective Longitudinal Study. Issue 9 (28th August 2018) - Schöffl, Volker Rainer; Hoffmann, Phillip Max; Imhoff, Andreas; Küpper, Thomas; Schöffl, Isabelle; Hochholzer, Thomas; Hinterwimmer, Stefan
Background: In the past few years, competition climbing has grown in popularity, and younger people are being drawn to the sport. Purpose: While radiographic changes in long-term climbers are known, there are little data available on adolescent climbers. The question arises as to whether climbing at high levels at a young age leads to radiographic changes and possibly an early onset of osteoarthritis of the finger joints. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 19 members of the German Junior National Team (GJNT group) and 18 recreational climbers (RC group) were examined clinically and radiographically in 1999. In 2011, these climbers were re-examined (mean follow-up, 11.3 ± 1.2 years). Radiographs were evaluated using a standard protocol, searching for physiological adaptations such as cortical thickness of the middle phalanx and an increased adopted Barnett-Nordin index, as well as for early-onset osteoarthritic changes of the hand. In contrast to the Kellgren-Lawrence scale, subchondral sclerosis was added to the group of physiological, adaptive stress reactions and was not defined as osteoarthritis. Osteoarthritis was defined by a Kellgren-Lawrence grade ≥2. Results: Overall, 15 of 19 (follow-up rate, 78.9%) climbers in the GJNT group and 13 of 18 in the RC group (follow-up rate, 72.2%), with a mean age of 26.8 years, were examined at the 11-year follow-up. Five climbers (33%) in the GJNT group presented with a decreased range of motion for the finger joints, in contrast to only 1 climber (8%) in the RC group. Radiographic stress reactions of the hand were found in 80% of the GJNT group and 46% of the RC group, including cortical hypertrophy (GJNT: 73%; RC: 23%), subchondral sclerosis (GJNT: 80%; RC: 31%), a broadened proximal interphalangeal joint base (GJNT: 67%; RC: 38%), and a broadened distal interphalangeal joint base (GJNT: 53%; RC: 31%). Training intensity in 1999 and body weight in 1999 were significant for the development of radiographic stress reactions in 2011 ( P < .05 for both). Signs of early-stage osteoarthritis were seen in 6 climbers: 4 (27%) in the GJNT group and 2 (15%) in the RC group. Significant statistical influences for the development of early-onset osteoarthritis were found for overall total training years ( P = .024), use of campus board training in 1999 ( P = .033), and climbing level ( P = .030). Conclusion: One-quarter of climbers who performed at a high level in their youth showed a "mild" form of osteoarthritis (Kellgren-Lawrence grade 2). In analyzing the training regimens of our climbers for longer than 10 years, we conclude that intensive finger training (eg, campus board training) can lead to early-onset osteoarthritis of the hand. We also demonstrate that a high Union Internationale des Associations d'Alpinisme (UIAA) climbing level correlates with the risk for early-onset osteoarthritis of the hand and therefore must be seen as a risk factor for developing early-onset osteoarthritis of the finger joints.